2020
DOI: 10.1161/jaha.119.015062
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Characteristics With Nocturnal Hypertension and Nondipping Blood Pressure in the CARDIA Study

Abstract: Background Sleep characteristics and disorders are associated with higher blood pressure ( BP ) when measured in the clinic setting. Methods and Results We tested whether self‐reported sleep characteristics and likelihood of obstructive sleep apnea ( OSA ) were associated with nocturnal hypertension and nondipping systolic BP ( SBP ) among participants in the CARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…Hypertension is present in up to 50% of patients with OSA, which is about double the prevalence of hypertension in general population studies [ 2 ]. A non-dipping nocturnal blood pressure (BP) profile (<10% day-to-night systolic blood pressure difference) is especially likely in OSA patients [ 3 6 ], even in the absence of significant hypertension. The likelihood of non-dipping BP correlates with OSA severity in population studies [ 7 ], and cardiovascular events are more frequent in OSA patients with a non-dipping BP profile than those with a normal dipping pattern, even in the absence of diagnosed hypertension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is present in up to 50% of patients with OSA, which is about double the prevalence of hypertension in general population studies [ 2 ]. A non-dipping nocturnal blood pressure (BP) profile (<10% day-to-night systolic blood pressure difference) is especially likely in OSA patients [ 3 6 ], even in the absence of significant hypertension. The likelihood of non-dipping BP correlates with OSA severity in population studies [ 7 ], and cardiovascular events are more frequent in OSA patients with a non-dipping BP profile than those with a normal dipping pattern, even in the absence of diagnosed hypertension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 , 18 ] The mechanisms involved in the morning increase in cardiovascular events have been unclear, but recent clinical studies have shown that an exaggerated morning BP surge is a plausible factor involved in the triggering of cardiovascular events, particularly in the case of stroke. [ 18 , 19 ] 1 mm Hg morning BP increase was associated with a 2.1% increased risk of cardiovascular death. [ 3 , 4 ] More and more evidences [ 20 22 ] show that the morning surge of blood pressure is closely related to cardiovascular events, stroke, and renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, blood pressure often decreases at night (i.e., nocturnal dipping) and lack of decrease (i.e., non-dipping), which is associated with increased risk of cardiovascular disease, 38 is more prevalent among individuals with sleep disturbances, such as obstructive sleep apnea and advanced sleep cycles. 39 The potential causal significance of poor sleep and its associations with adverse health outcomes are reinforced by several prospective studies 17,15,16 /reviews. 14,30 However, though there are several biological pathways through which sleep patterns and sleep disturbances could affect chronic health conditions, these relationships and their directions have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Other physiological processes follow diurnal patterns and may be disrupted by sleep disturbances. For instance, blood pressure often decreases at night (i.e., nocturnal dipping) and lack of decrease (i.e., non‐dipping), which is associated with increased risk of cardiovascular disease, 38 is more prevalent among individuals with sleep disturbances, such as obstructive sleep apnea and advanced sleep cycles 39 …”
Section: Discussionmentioning
confidence: 99%